Overeducation in Europe: Trends, Convergence and Drivers - Seamus McGuinness; Adele Bergin; Adele Whelan (Institute of Labor Economics (IZA), 2017)
This paper examines patterns in overeducation between countries using a specifically designed panel dataset constructed from the quarterly Labour Force Surveys of 28 EU countries over a twelve to fifteen year period. It is not the case that overeducation has been rising rapidly over time in all countries and where overeducation has grown the trend has been very gradual. Furthermore, overeducation rates were found to be static or falling in approximately fifty percent of the 28 EU countries. The evidence points towards convergence in overeducation at a rate of 3.3 percent per annum. In terms of the determinants of overeducation we find evidence to support policies aimed at improving effective female participation, labour market flexibility and the practical aspects of educational provision as a means of reducing the incidence of overeducation within countries.
Keywords: I2; C23; 330; overeducation; dynamic panel data